Communication Ethics Between Husband and Wife from the Perspective of Sufistic Morality and Its Implications for Family Harmony - Acep Nurullah; Badrudin Kamil (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Communication between spouses serves as the primary medium determining the quality of marital relationships, functioning not merely as information exchange but as the continuous construction and reconstruction of shared meaning, trust, and emotional safety. Despite extensive scholarship on marital communication from interpersonal communication and marital psychology perspectives, studies that systematically examine spousal communication ethics through the lens of akhlaq tasawuf as a coherent normative system remain scarce. This study aims to construct a comprehensive framework of spousal communication ethics based on five core akhlaq tasawuf principles—shidq (authentic truthfulness), amanah (sacred trustworthiness), hilm (composed gentleness), tawadu' (authentic humility), and husnuzh-zhann (charitable interpretation)—and to analyze their implications for marital harmony. Employing a qualitative normative-integrative library research methodology that dialogizes classical Sufi texts with contemporary interpersonal communication theory and marital psychology, this study finds that the five principles form a coherent, mutually reinforcing value system that collectively produces 'communicative sakinah'—a state of relational tranquility generated through honesty, trust, and humility in every spousal interaction. Crucially, these principles demonstrate strong resonance with Gottman's marital research, Rogers' client-centered communication theory, and Nonviolent Communication (NVC), confirming that akhlaq tasawuf wisdom is empirically validated beyond normative-religious boundaries. The study proposes the Communicative Sakinah Model as a practical framework for marriage preparation, couple counseling, and family harmony programs